After Sales Business Process Optimization (Universitas Negeri Semarang, 2021)
In managing a business, service to customers is something that cannot be underestimated. Customer satisfaction with the services provided will affect whether in the future the customer will conduct transactions again in the business or will choose other services that are more satisfying. After-sales service or after-sales service is a service that is rarely provided by a business to consumers. However, this service is an important service to find out how the level of customer satisfaction with the products of the business. In this study, we will describe the optimization of after-sales services in an SME printing business as a case study. This research will use descriptive research methods with survey data collection methods and literature study. Respondents are customers who have made transactions in this SME printing business.